2013
DOI: 10.1016/j.brat.2013.07.005
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of Behavioral Activation (BA) therapy for improving psychological and physical health in dementia caregivers: Results of the Pleasant Events Program (PEP)

Abstract: Dementia caregiving is associated with elevations in depressive symptoms and increased risk for cardiovascular diseases (CVD). This study evaluated the efficacy of the Pleasant Events Program (PEP), a 6-week Behavioral Activation intervention designed to reduce CVD risk and depressive symptoms in caregivers. One hundred dementia family caregivers were randomized to either the 6-week PEP intervention (N=49) or a time-equivalent Information-Support (IS) control condition (N=51). Assessments were completed pre- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
75
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 74 publications
(90 reference statements)
3
75
1
3
Order By: Relevance
“…It is also one of the few studies demonstrating an effect of a caregiving intervention on physiological indicators of stress. 37 Although effect size was small, these results suggest the value of broadening the focus of caregiver interventions to include their impact on relevant biological risk factors associated with chronic stress and disease.…”
Section: Discussionmentioning
confidence: 91%
“…It is also one of the few studies demonstrating an effect of a caregiving intervention on physiological indicators of stress. 37 Although effect size was small, these results suggest the value of broadening the focus of caregiver interventions to include their impact on relevant biological risk factors associated with chronic stress and disease.…”
Section: Discussionmentioning
confidence: 91%
“…Another study found that older adults who participated in a 10-week intervention to enhance perceived control demonstrated increased personal mastery and reduced psychological distress compared with control participants (Reich & Zautra, 1989). Caregiver interventions specifically targeting activity restriction have been rare, although Moore et al (2013) found that a brief intervention (four in-home and two phone sessions) aimed at increasing dementia caregivers’ engagement in pleasant activities resulted in decreased depressive symptoms compared with an information and support control condition. The results of the present study indicate that increased personal mastery and decreased activity restriction mediate post-placement improvements in caregiver depressive symptoms over time.…”
Section: Discussionmentioning
confidence: 99%
“…The groups chose the topic chapters for the remaining eight sessions Moore et al (2013) RCT with two groups: PEP intervention or a time-equivalent Information-Support (IS) control condition 100 Pleasant Events Program At 6-week follow-up, intervention group had significantly greater reductions in Interleukin-6, depression, and negative affect. At 1-year follow-up, no statistically significant outcomes were reported …”
Section: Caregiver Outcomesmentioning
confidence: 99%